Knowledge transmission channels: a comparative study of clusters in Brazil and in China - Sohn, Ana Paula Lisboa (2013)
The aim of this paper is to identify and analyze the knowledge transmission channels in two textile clusters located in two emerging economies: one in Vale do Itajaí, in Brazil, and the other in Haining, in China, highlighting the existing similarities and discrepancies. Information in the textile cluster in Brazil was collected through: studies on secondary sources and fieldwork. The characterization and identification of knowledge transmission channels most used in cluster in Chinese cluster were based on survey data collected from secondary sources, namely research published by international organizations. In both clusters, opportunities of direct learning are found with other companies operating in the same market can be restricted due to the similarity between the goods and a limited competitiveness. The results show that the relations with competitors, suppliers and customers are important knowledge transmission channels in textile clusters. This research can be used by managers to enable the understanding of the mechanisms and determinants of knowledge transmission channels and can also influence the knowledge diffusion more effectively.